Wpływ zmian cen i dochodów na zakupy artykułów do produkcji rolnej - Brojerski, Marek (Wydział Prawa i Administracji UAM, 1973)
The main aim of this article is to present relations between the extent of the supply with articles for agricultural production on one side and the changes of pur chaise prices of agricultural products and meams of production prices on the other. Relations appearing in this field are of mutual operation kind. We can assume that under definite conditions of agricultural policy the increase in production and changes of prices profitable for farmers are the premise of the increase in production supplies. We also took into consideration the relations between the demand for articles used for agricultural production and the formation of incomes of agricultural population. In case of fluctuation of these incomes, especially on the territories of low production intensification, there is need of applying the whole range of economic devices to ensure sale of articles for agricultural production.
Influence of the Change of Prices and Incomes on Buying Articles Used for Agricultural Production